The beginner's guide to decorating pottery : an introduction to glazes, patterns, inlay, luster, and dimensional designs - Reinhardt, Emily (Essential ceramics skills., 2023)
"With The Beginner's Guide to Decorating Pottery, learn to create designs and patterns on clay that have a distinctive, modern feel and are easy enough for beginners to master"--